The Neoliberal Agenda and the Changing Urban Form of Istanbul - Enlil, Zeynep Merey (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2011)
In the new era of competition among cities - globally - Istanbul has become once again the focus of Turkey's economic development effort. The dissolution of the Soviet Bloc and the growth of economic and cultural linkages between the Turkic-speaking states, plus the turbulent dynamics of the Middle East, have created a new macro-regional environment. There is no other major city centre to compete with Istanbul in a vast area stretching from the Balkans to the Caucasus, the Ukraine to Lebanon. Istanbul's size, history and location meant it was bound to play an increasingly prominent role as regional trade, networks and incomes became more interconnected. Although Istanbul is not the formal capital of Turkey, it is far and away Turkey's largest and most important urban concentration. As such, the Turkish state has allocated it central role in its vision for economic and cultural transformation. This paper traces the footprints in Istanbul of the unfolding 'project' of Turkish integration with the world economy. Following a brief outline of the history of the city since the nineteenth century, it focuses on recent attempts to reposition the country in the global arena, and highlights their ramifications for the urban form of Istanbul.
Keywords: Public Administration